How to define 'best practice' for use in Knowledge Translation research: a practical, stepped and interactive process. Issue 5 (9th April 2012) - Bosch, Marije; Tavender, Emma; Bragge, Peter; Gruen, Russell; Green, Sally
Abstract Objectives Defining 'best practice' is one of the first and crucial steps in any Knowledge Translation (KT) research project. Without a sound understanding of what exactly should happen in practice, it is impossible to measure the extent of existing gaps between 'desired' and 'actual' care, set implementation goals, and monitor performance. The aim of this paper is to present a practical, stepped and interactive process to develop best practice recommendations that are actionable, locally applicable and in line with the best available research‐based evidence, with a view to adapt these into process measures (quality indicators) for KT research purposes. Methods Our process encompasses the following steps: (1) identify current, high‐quality clinical practice guidelines (CPGs) and extract recommendations; (2) select strong recommendations in key clinical management areas; (3) update evidence and create evidence overviews; (4) discuss evidence and produce agreed 'evidence statements'; (5) discuss the relevance of the evidence with local stakeholders; and (6) develop locally applicable actionable best practice recommendations, suitable for use as the basis of quality indicators. Conclusions Actionable definitions of local best practice are a prerequisite for doing KT research. As substantial resources go into rigorously synthesizing evidence and developing CPGs, it is important to make best use of such available resources. We developed a process for efficiently developing locally applicable actionable best practice recommendations from existing high‐quality CPGs that are in line with current research evidence.